USAHA PERBANKAN DALAM MENGATASI CREDIT CRUNCH PERBANKAN DI INDONESIA DENGAN MENGIKUTI KEBIJAKAN PEMERINTAH DAN KREDIT SELEKTIF MENGGUNAKAN PRINSIP 5 C - Margono, Bagus (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This study aims to determine the development of the use of bank funds for credit and non-credit from 2000 to 2021 with the occurrence of a credit crunch, to determine government policies in overcoming credit crunch in banks, and to analyze bank selective credit by applying the five C's of credit in the banking sector. in developing credit to the community. The data were analyzed using descriptive analysis based on these data.Based on the results of the analysis, banks initially invested in non-credit, namely in the form of purchasing securities and the like from 2000 to 2012 ranging from 0.13 or 13% to 0.19 or 19% except for 2005 35%. However, starting in 2013 there was an increase in investment in the non-credit sector, between 29% and 35%. This investment has a fixed advantage that comes from interest. This bank's concern has increased during the Covid 19 Pandemic since March 2020. %. In 2020 there was a decline in credit of 2% and in 2021 (until April) the increase in credit was relatively constant. Total loans in 2020 amounted to Rp 5,547,618 billion while in 2021 (until April) it decreased to Rp 5,543.3 billion or a decrease of 0.076 %. This is the impact of the bank's concern about bad loans, causing a credit crunch. Banks prefer funds in the non-credit sector Banks need to follow government advice to lower lending rates and use export and import financing institutions and PT. Indonesia Infrastructure Guarantee to be able to obtain guarantees for loans provided by the government. In addition, banks need to conduct a 5C analysis on company credit applications, especially in the food, service and telecommunications sectors.